Development of Liquid Target System Based on 14 MeV Cyclotron Isotope 18F Production - Fei WANG; Li LING; Guofang SONG; Xianlu JIA; Guang YANG; Lijie ZHAO; Peng HUANG; Shigang HOU; He ZHANG; Pengfei ZHU; Jie LIU (Journal of Isotopes, 2024)
Based on the excellent radionuclide properties of 18F，amino acids labeled with radioactive nuclide 18F have shown its unique advantages in brain tumor imaging. A liquid target system with niobium as the target material and 18O(p，n)18F isotope was developed based on the 14 MeV cyclotron of the cyclotron research group of the Department of Nuclear Technology and Application，China Institute of Atomic Energy. In order to solve the problems of complicated structure and poor cooling effect of liquid target system cooled by helium，a liquid target system with direct water cooling is designed. The structure design process and material selection of liquid target are introduced in detail，and the stability of its transport system and control system is tested. The analysis results show that the liquid target system produced by this isotope has good stability. Under the irradiation of 20 μA beam intensity for 2 h，the yield of the product is 1.5 Ci. At present，it has been applied in Peking University，the system has good stability and repeatability，and has been highly praised by users.